The human edge : how curiosity and creativity are your superpowers in the digital economy - Orme, Greg (Pearson, 2019)
"This text has been prompted by the impact of technology, but it's not about microchips, databases and algorithms. It's about humans. Particularly, humans' response to how AI is transforming our world. The author offers a development path through this emerging landscape. In a world that's changing at a dizzying pace, the text encourages to become an even more human human"--